Pergulatan Sains dan Agama - Edwin Syarif (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2013)
This paper describes the struggle of science and religion with a historical approach. The relation of both subjects has occurred in four periods: Greek, Islamic, Renaissance and Modern eras. Grouping into four sections is intended for the easy analysis, of the struggle between science and religion, so one can know the different characteristics.DOI: 10.15408/ref.v13i5.917